Results of Using Different Brain Reperfusion Methods in Patients with Acute Ischemic Stroke - A. G. Khadisova; T. V. Zakhmatova; T. V. Sergeeva (Вестник рентгенологии и радиологии, 2024)
Acute ischemic stroke (AIS) occupies one of the leading places in the structure of disability and mortality in adult population throughout the world, which causes a significant social and economic burden of this pathology. Recent advances in AIS diagnosis and treatment have significantly reduced mortality and improved functional outcomes in patients. However, categories of patients with unsatisfactory results and complications of reperfusion therapy still remain. In some of them, mortality may exceed the overall rate. To this day, there are controversial aspects in determining indications and choosing the preferred method of cerebral reperfusion. The presented cases describe the results of using thrombolytic therapy and thromboextraction in AIS patients of different age groups. The importance of various neuroimaging methods (multislice computed tomography, computed angiography, duplex ultrasound of extra- and intracranial arteries) for timely diagnosis and determination of optimal revascularization tactics was noted.